แนวทางการพัฒนาสภาพแวดล้อมของรีสอร์ทเพื่อสุขภาพในการดูแลสุขภาพแบบองค์รวม ในช่วงวิกฤตโควิด-19 - ณัฐชานันท์ สิริปิยพัทธ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2022)
Wellness tourism is a new type of tourism in Thailand that interests both Thai and foreign tourists interested in utilizing the services of Thai health resorts, each according to their own objectives. During the COVID-19 pandemic, Thai health resorts were significantly impacted and needed to adapt to overcome this crisis. The purpose of this research article is to study the adaptation guidelines of health resorts during the COVID-19 pandemic, including risk management, target markets, marketing, services, internal organizational characteristics, and guidelines for the future development of health resorts in response to similar situations. This qualitative research study includes three case studies and involved in-depth interviews with 4 entrepreneurs or executives, 2 medical specialists, and 30 health resort consumers, for a total of 36 participants. The study found that 1) the target group for health resorts during the COVID-19 pandemic consisted mostly of domestic Thai tourists; 2) in terms of the health resorts’ marketing strategies, prices and activities had to be adjusted to suit Thai tourists; 3)consumers showed greater interest in health-related travel behavior, influenced primarily by price, followed by internal health resort service; 4) the medical specialists expressed the opinion that health tourism and the number of health resorts in Thailand will continue to grow after the COVID-19 pandemic. This research illustrated the adaptation strategies health resorts resorted to during the COVID-19 pandemic. However, it is recommended that the government have a policy to provide greater short- and long-term assistance to entrepreneurs in Thailand s tourism sector during times of crisis.